Streamlining organizational processes through AI, IoT, blockchain, and virtual environments - Hernández Hernández, Marisol 1971- (Advances in business information systems and analytics, 2023)
"The objective of this book will be to propose optimization strategies in organizations, through technologies such as AI, IoT, Blockchain, and Virtual Environments. It will be written for professionals who wish to improve their knowledge regarding the adaptation of this type of technology in their production processes and/or services in public or private organizations, or who need to implement some ideas in their academic fields or their work areas"--